2020
DOI: 10.35542/osf.io/u263b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated Educative Nudges to Reduce Missed Assignments in College

Abstract: As institutions of higher education increasingly utilize online learning management systems, college students are asked to submit more assignments online. Under this regime, when most assignments are posted and submitted online, it is possible to know if a student is missing a submission for an imminent deadline, and to intervene proactively to reduce missed assignments and improve student outcomes. Toward this goal, we designed and evaluated a scalable targeted intervention: a mobile app that would deploy pus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Of which, ten studies were selected in this review after the screening. The ten studies covered diverse areas ( setting and problem ) that included evaluating the effects of self‐directed scheduling (Baker et al, 2016), improving cooperative learning (Buchs et al, 2016), enhancing learning experiences and outcomes (Dart & Spratt, 2020), reducing procrastination in a competitive learning environment (Li et al, 2021), informing on imminent submission deadlines (Motz et al, 2021), persuading students to improve their study consistency (O'Connell & Lang, 2018), evaluating the impact on procrastination (Onji & Kikuchi, 2011), improving the enrolment rate of tutoring services (Pugatch & Wilson, 2018), evaluating the impact of learning outcome (Sinha et al, 2021), and improving task performance (Smith et al, 2018). These ten included studies were published between 2011 to 2021 across six different countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of which, ten studies were selected in this review after the screening. The ten studies covered diverse areas ( setting and problem ) that included evaluating the effects of self‐directed scheduling (Baker et al, 2016), improving cooperative learning (Buchs et al, 2016), enhancing learning experiences and outcomes (Dart & Spratt, 2020), reducing procrastination in a competitive learning environment (Li et al, 2021), informing on imminent submission deadlines (Motz et al, 2021), persuading students to improve their study consistency (O'Connell & Lang, 2018), evaluating the impact on procrastination (Onji & Kikuchi, 2011), improving the enrolment rate of tutoring services (Pugatch & Wilson, 2018), evaluating the impact of learning outcome (Sinha et al, 2021), and improving task performance (Smith et al, 2018). These ten included studies were published between 2011 to 2021 across six different countries.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies fulfilled all the MMAT criteria (Dart & Spratt, 2020; Li et al, 2021; O'Connell & Lang, 2018; Pugatch & Wilson, 2018; Smith et al, 2018). Another four were unable to fulfil the randomisation criteria (MMAT 2.1) in the quantitative RCT category as the studies did not specify how the randomisation schedule were generated (Baker et al, 2016; Buchs et al, 2016; Motz et al, 2021; Sinha et al, 2021), and one did not account for the confounders (MMAT 3.4) in the quantitative non‐randomised category (Onji & Kikuchi, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the Spring 2019 semester, regardless of condition assignment for the current study, all app users received notifications about imminent deadlines, recent instructor announcements, and upcoming calendar events according to their preferences within the app (for additional details, see Motz, Mallon, and Quick, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Still, it is likely advantageous to learning to have the wearer attempt to self-generate an answer rather than to recognize it from among a set of options (Rowland, 2014), and nothing precludes mentally generating longer answers on the part of the wearer. Moreover, Heitmayer and Lahlou (2021) recently showed that only 11% of smartphone interactions are notification-initiated, pointing toward another potential advantage of smartwatches over smartphones for uses requiring frequent notifications, including other forms of education-related nudges (e.g., Motz, Canning, Green, Quick, & Mallon, 2020a; Motz, Mallon, & Quick, 2020b). Therefore, future research should compare smartwatch to smartphone delivery formats.…”
Section: Future Researchmentioning
confidence: 99%